The Motility, Viability, and Abnormality of the Frozen Bali Bull Semen with Andromed and Egg yolk-Tris Extender: Quality of Bali Bull Semen - Nur Salmah; Toleng Abd Latief; Muhammad Yusuf; Masturi; Sahiruddin; Hasrin; Masir Ummul (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2021)
The research compared the quality of frozen semen (motility, sperm live-cell and spermatozoa abnormality) of Bali Cattle on andromed and tris egg yolk (TKT) diluent. This research used one of the Balinese Bull. Semen was collected five times for two diluent treatments, which was P1= andromed+ aquadest and P2= TKT + glycerol. The parameters measured were motility, sperm live-cell and abnormalities of spermatozoa. Each parameter in each treatment was compared using the T-test (t-test independent sample). This research indicated that P1 was better able to maintain with P2, motility and the percentage of sperm live-cell frozen semen spermatozoa in andromed diluent is still above 40% is 50.8, 6.14% and TKT is 5.03% and a TKT of 33,3 %; 2,64 %. There was no significant difference in abnormalities of frozen semen Bali cows in the two diluents which the respective values for andromed and TKT were 13,2 %; 2,73%; and 14.3 %; 3.51%. It can be concluded that TKT still needs improvement to reach 40% or more.